Psychological autopsy study comparing suicide decedents with and without a history of suicide attempts in a nationwide sample of South Korea. Issue 2 (3rd April 2021) - Yook, Vidal; Kim, Hyewon; Kim, Eun Ji; Kim, Yuwon; Lee, Gusang; Choi, Jin Hwa; Shin, Myung‐Hee; Jeon, Hong Jin
Abstract: The majority of suicide decedents die on their initial attempt. To bring attention to suicide decedents without a suicide attempt history, the current study explored their demographic, clinical, and suicide‐related characteristics. The data were derived from the Korea National Investigation of Suicide Victims Study, which assessed all suicide cases from 2013 to 2017 recorded in police investigation reports. We compared suicide decedents with and without a history of nonfatal attempts using the Korea Psychological Autopsy Checklist for Police Records (K‐PAC). Out of 5228 cases included in our study, 3147 (60.2%) died on their first suicide attempt. Demographically, those who were male, older than 65, employed, and married/widowed were more likely to die on their initial attempt. Clinically, those who died on their initial attempt were more likely to have never been diagnosed with psychiatric disorders, whereas those who died on a repeated attempt were more likely to have been diagnosed with mood disorders. In terms of suicide‐related factors, experiencing relationship problems and complaining about physical discomfort were associated with dying on an initial attempt. Depressed affect, self‐harming behaviors, and talking about suicide or death were associated with repeated attempts.